ffects of green and black tea biocomposites on endogenous synthesis, metabolism and genotoxic effect of carcinogenic N-nitrosodimethylamine - Glavin, O.A.; Mikhailenko, P.M.; Zaletok, S.P.; Gulua, L. (Experimental Oncology, 2008)
Aim: To study the modifying effect of green and black tea biocomposites on endogenous synthesis and genotoxic action of the carcinogenic N-nitrosodimethylamine. Methods: Green and black tea biocomposites were administered to the white inbred rats in vivo. Amidopyrine and sodium nitrite were used as N-nitrosodimethylamine precursors and 4-methylpyrazol as an inhibitor of its metabolism. N-nitrosodimethylamine (blood, daily urine and reaction mixture), nitrites and nitrates (daily urine) levels were measured. Genotoxic action was tested by formation of DNA single-strand breaks in hepatocytes. Results: In in vitro system, biocomposites increased N-nitrosodimethylamine synthesis in neutral medium and decreased in acid conditions. In vivo, black tea biocomposite consumption resulted in enhanced background level of DNA single-strand breaks in rats hepatocytes and higher genotoxic effect upon administration of N-nitrosodimethylamine precursors. The levels of N-nitrosodimethylamine in blood and urine of experimental animals were increased after precursors’ administration. In contrast, green tea biocomposite significantly decreased background level of DNA single-strand breaks. However, there was no protective action of this food supplement at the N-nitrosodimethylamine, precursors’ administration. 4-methylpyrazol administration did not increase N-nitrosodimethylamine excretion in urine, while this effect was observed in control and black tea biocomposite groups. Conclusions: The effects of green tea and black tea biocomposites on N-nitrosodimethylamine synthesis in in vitro system are unidirectional and depend on biocomposites’ concentration and acidity of the medium. Long-term consumption of black tea biocomposite resulted in intensification of endogenous N-nitrosodimethylamine synthesis and increased damage of the hepatocytes’ DNA. As to the green tea biocomposite, the obtained results allow us to suggest that this biocomposite enhanced N-nitrosodimethylamine metabolism. Цель: изучить модифицирующий эффект биокомпозитов из зеленого и черного чая на эндогенный синтез и генотоксическое действие канцерогенного N-нитрозодиметиламина. Методы: в эксперименте in vivo белые нелинейные крысы получали биокомпозиты из зеленого и черного чая. Амидопирин и нитрит натрия использовали в качестве предшественников N-нитрозодиметиламина и 4-метилпиразол в качестве ингибитора его метаболизма. Измеряли содержание N-нитрозодиметиламина (кровь, суточная моча и реакционная смесь), нитритов и нитратов (суточная моча). Генотоксическое действие оценивали по образованию однонитевых разрывов ДНК в гепатоцитах. Результаты: в системе in vitro биокомпозиты повышали синтез N-нитрозодиметиламина при нейтральной кислотности реакционной среды и снижали его в кислых условиях. В эксперименте in vivo употребление крысами биокомпозита из черного чая приводило к повышению уровня однонитевых разрывов ДНК в гепатоцитах и повышало генотоксический эффект от введения предшественников N-нитрозодиметиламина. После введения предшественников содержание N-нитрозодиметиламина в крови и моче было повышено. Наоборот, биокомпозит из зеленого чая значительно снижал фоновый уровень однонитевых разрывов ДНК. Однако не отмечали защитного действия этой пищевой добавки при введении предшественников N-нитрозодиметиламина. Введение 4-метилпиразола не приводило к повышенной экскреции N-нитрозодиметиламина с мочой, хотя этот эффект отмечали в контрольной группе и группе с назначением биокомпозита из черного чая. Выводы: в системе in vitro биокомпозиты из зеленого и черного чая однонаправлено влияли на синтез N-нитрозодиметиламина, а их эффекты зависели от кислотности реакционной среды и концентрации в ней биокомпозитов. Длительное употребление биокомпозита из черного чая приводило к интенсификации эндогенного синтеза N-нитрозодиметиламина и повышало уровень повреждений ДНК в гепатоцитах. Результаты, полученные относительно биокомпозита из зеленого чая, позволяют нам предположить, что он повышал метаболизм N-нитрозодиметиламина.